Survival after allogeneic transplantation according to pretransplant minimal residual disease and conditioning intensity in patients with acute myeloid leukemia - Núñez-Torrón Stock, Claudia; Jiménez Chillón, Carlos; Martín Moro, Fernando; Marquet Palomanes, Juan; Piris Villaespesa, Miguel; Roldán Santiago, Ernesto; Rodríguez Martín, Eulalia; Chinea Rodríguez, Anabelle; García Gutiérrez, Valentín; Moreno Jiménez, Gemma; López Jiménez, Javier; Herrera Puente, Pilar (Frontiers in Oncology, 2024)
Background The measurement of minimal residual disease (MRD) by multiparametric flow cytometry (MFC) before hematopoietic stem cell transplantation (HSCT) in patients with acute myeloid leukemia (AML) is a powerful prognostic factor. The interaction of pretransplant MRD and the conditioning intensity has not yet been clarified. Objective The aim of this study is to analyze the transplant outcomes of patients with AML who underwent HSCT in complete remission (CR), comparing patients with positive MRD (MRD+) and negative MRD (MRD−) before HSCT, and the interaction between conditioning intensity and pre-HSCT MRD. Study design We retrospectively analyzed the transplant outcomes of 118 patients with AML who underwent HSCT in CR in a single institution, comparing patients with MRD+ and MRD− before HSCT using a cutoff of 0.1% on MFC, and the interaction between conditioning intensity and pre-HSCT MRD. Results Patients with MRD+ before HSCT had a significantly worse 2-year (2y) event-free survival (EFS) (56.5% vs. 32.0%, p = 0.018) than MRD− patients, due to a higher cumulative incidence of relapse (CIR) at 2 years (49.0% vs. 18.0%, p = 0.002), with no differences in transplant-related mortality (TRM) (2y-TRM, 19.0% and 25.0%, respectively, p = 0.588). In the analysis stratified by conditioning intensity, in patients who received MAC, those with MRD− before HSCT had better EFS (p = 0.009) and overall survival (OS) (p = 0.070) due to lower CIR (p = 0.004) than MRD+ patients. On the other hand, the survival was similar in reduced intensity conditioning (RIC) patients regardless of the MRD status. Conclusions Patients with MRD+ before HSCT have worse outcomes than MRD− patients. In patients who received MAC, MRD− patients have better EFS and OS due to lower CIR than MRD+ patients, probably because they represent a more chemo-sensitive group. However, among RIC patients, results were similar regardless of the MRD status.